PERCEPTIONS OF MEDICAL DOCTORS ON REFUGEES’ HEALTH SEEKING BEHAVIOURS IN DURBAN SOUTH AFRICA - Zihindula, Ganzamungu (European Scientific Journal, ESJ, 2015)
The available literature on refugees’ health care seeking behaviours does not address the perceptions of medical doctors providing health services, yet doctors are likely to understand the refugees’ health issues well. The aim of this study was to explore medical doctors’ perceptions of health care seeking behaviours of refugees from the Democratic Republic of Congo (DRC) in Durban, South Africa. A qualitative approach was adopted consisting of in-depth interviews with four medical doctors practicing in the private sector. The results revealed that after failing to access health care services from public hospitals, refugees alternatively seek the same services from private practices, where they are compelled to pay a fee for these services. Refugees reported avoiding public hospitals due to mistrust, avoidance of stressors, miscommunication and non-possession of identity documents (which are a requirement in public health facilities), and their unmet cultural expectations. Findings suggest that refugees seek private health care services despite this being an additional financial burden to an already economically disempowered population group. This calls for cultural awareness, training and adoption of health care-communication facilitators, and building trust between health providers and patients in public hospitals.